(untitled) (Latakia University Journal -Basic Sciences Series, 2020)
In this research, we have measured the concentration of potassium and cesium elements of citrus fruits from different sources in Tartous (Akkar plain), by using scintillation detector where it was found that the minimum value of The effectiveness of radiation for potassium amounted to 6.11 Bq / L while the highest value it is 38.20 Bq / L, was the potassium concentration account by using a flame technology shows that the minimum value of potassium concentration is 0.044ppm and the highest value is 0.270ppm. It has been found that all samples were not contaminated by Cesium. The results obtained were compared in both radiological and Chemical ways where the results showed a good match.